Produção de carvão ativado de resíduos de grãos de canola visando remediação de recursos hídricos contaminados por metais tóxicos - Schiller, Andréia da Paz (2019)
The agroindustry waste has high adsorbent potential for the toxic metals removal from water and if it receive chemical, physical and thermal modifications, the toxic metals removal can be increased. The objective of this study was to evaluate the use of canola grain residues as precursor material to produce chemically and physically activated carbons and to evaluate these adsorbent materials in the sorption of Cd2+ and Pb2+ metal ions from contaminated water. For this, activated carbons were developed with NaOH, ZnCl2, H3PO4 e CO2, giving rise to 9 adsorbents materials that were characterized in terms of chemical element content, structural aspects (infrared spectroscopy – FTIR), morphological aspects (scanning electron microscopy – SEM), point of zero charge (pHPZC), thermal stability (TG/DTG), surface area, pore size and volume (estimated by BET and BJH). After this step, evaluations were performed to determine the optimal sorption conditions (pH versus adsorbent dose) by means of multivariable analysis through the adoption of central composite rotatable design (CCRD). The adsorption kinetics were evaluated using linear and non-linear mathematical models of pseudo-first order, pseudosecond order, Elovich and intraparticle diffusion. Adsorption isotherms were calculated according to linear and non-linear mathematical models of Langmuir, Freundlich, DubininRadushkevich (D-R) and Sips. The effect of initial concentration, adsorption thermodynamic and the desorption also were study. According to the SEM it was observed that the carbons produced had regular and well-formed structures with good porosity, and the FTIR observed the presence of hydroxyl groups, aliphatic, phenolic, carboxylic, inferring that the adsorbents has characteristics favorable to adsorption. The chemical modifications (NaOH, ZnCl2 and H3PO4 – 1 mol L-1), physical modification (CO2) and pyrolysis (temperature up to 750 ºC) changed the point of zero charge of the tested adsorbents. The optimal sorption conditions of the Cd2+ and Pb2+ ions were: pH: 5.0; adsorbent mass: 4 g L-1 and 40 min mean equilibration time for all the adsorbents tested. In general, the pseudo-second order and D-R models suggested the predominance of physical sorption, and the best mathematical adjustments (R2) occurred by non-linear models. The highest removal efficiency occurred in all cases for the lowest doses of adsorbents evaluated, with high desorption rates for Cd2+ and Pb2+. Most of the materials conformed to the Langmuir, Freundlich and D-R models, suggesting the occurrence of physical adsorption in mono and multilayer. The thermodynamics study showed that the processes were mostly spontaneous or became spontaneous as the temperature increases and pointed to the occurrence of physical adsorption. However, it is possible to infer that the activated carbons have an even greater potential for the removal efficiency of Cd2+ and Pb2+ when compared to their precursor biosorbents. In addition, future studies aimed at evaluating other process variables, such as temperature and time of pyrolysis are desirable, considering that the residual biomass of canola presents extremely production of modified adsorbents.